Global budget and radiative forcing of black carbon aerosol: Constraints from pole‐to‐pole (HIPPO) observations across the Pacific. Issue 1 (14th January 2014) - Wang, Qiaoqiao; Jacob, Daniel J.; Spackman, J. Ryan; Perring, Anne E.; Schwarz, Joshua P.; Moteki, Nobuhiro; Marais, Eloïse A.; Ge, Cui; Wang, Jun; Barrett, Steven R. H.
Abstract [1] We use a global chemical transport model (GEOS‐Chem) to interpret aircraft curtain observations of black carbon (BC) aerosol over the Pacific from 85°N to 67°S during the 2009–2011 HIAPER (High‐Performance Instrumented Airborne Platform for Environmental Research) Pole‐to‐Pole Observations (HIPPO) campaigns. Observed concentrations are very low, implying much more efficient scavenging than is usually implemented in models. Our simulation with a global source of 6.5 Tg a−1 and mean tropospheric lifetime of 4.2 days (versus 6.8 ± 1.8 days for the Aerosol Comparisons between Observations and Models (AeroCom) models) successfully simulates BC concentrations in source regions and continental outflow and captures the principal features of the HIPPO data but is still higher by a factor of 2 (1.48 for column loads) over the Pacific. It underestimates BC absorbing aerosol optical depths (AAODs) from the Aerosol Robotic Network by 32% on a global basis. Only 8.7% of global BC loading in GEOS‐Chem is above 5 km, versus 21 ± 11% for the AeroCom models, with important implications for radiative forcing estimates. Our simulation yields a global BC burden of 77 Gg, a global mean BC AAOD of 0.0017, and a top‐of‐atmosphere direct radiative forcing (TOA DRF) of 0.19 W m−2, with a range of 0.17–0.31 W m−2 based on uncertainties in the BC atmospheric distribution. Our TOA DRF is lower than previous estimates (0.27 ± 0.06 W m−2 in AeroCom, 0.65–0.9 W m−2 in more recent studies). We argue that these previous estimates are biased high because of excessive BC concentrations over the oceans and in the free troposphere.